Impact of Se in Structural, Mechanical, Thermal, Thermoelectric and Optical Properties of n-type SnTe. (23rd July 2021) - Muthumari, M.; Manjula, M.; Pradheepa, K.; Kuznetsov, Denis; Veluswamy, Pandiyarasan
Abstract : Lead-free SnTe compound is an alternative material for thermoelectric devices offering suitable band gap, non-toxicity, and mechanical stability. Here the structural, electronic, mechanical, thermal, thermoelectric, and optical properties of parent binary SnTe and ternary SnTe0.125 Se0.875, SnTe0.25 Se0.75, SnTe0.5 Se0.5, SnTe0.75 Se0.25, SnTe0.875 Se0.125 materials are discussed at ambient conditions using full-potential linearized augmented plane wave method based on density functional theory. To make an accurate band gap we have used the mBJ scheme for the parent compound. The stability of the materials was confirmed using their calculated elastic constants. From the calculated mechanical properties, we have noted that the SnTe0.25 Se0.75 material is more ductile and the SnTe0.875 Se0.125 material has more hardness and a more brittle nature compared to other materials. We have computed the Seebeck coefficient, electrical conductivity, and power factor value in the temperature range of 300 to 1000 K in steps of 100 K using Boltzmann transport theory interfaced with the Wien2k program. From the thermoelectric properties, the ternary SnTe0.5 Se0.5 havs a high power factor due to maximum electrical conductivity and is identified as a potential compound for thermoelectric applications. From the calculated optical results, the series of SnTe combinations are deemed suitable materials for optoelectronic applications. Our theoretical results are agreed well with available experimental results.